Evaluating the protective impact of pumpkin seeds oil against ciprofloxacin induced hepatorenal toxicity in the male albino rats - Sabry Abd El-Shafi Ahmed, Hanan; A. A.Elkomy, Ashraf; A.H. Farag, Enas (International Journal of Pharmacology and Toxicology, 2022)
Background: Ciprofloxacin increased the production of reactive oxygen species, As a result of its intracellular accumulation, which leads to extracellular membrane damage, resulting in the release of apoptotic components into the bloodstream, a condition known as apoptosis. Objective: The goal of this study is to investigate the protective effect of pumpkin seeds oil (PSO), a well-known natural antioxidant against Ciprofloxacin-induced liver and kidney impairment (CPFX[i]). Material and methods: Forty-Four male albino rats weighing approximately 180â€“200 gm were formed. (n = 10): (1) control saline, (2) PSO [ii] (4ml/kg/day orally for 4 weeks), (3) CPFX (80mg/kg/day orally for 2 weeks), and (4) PSO (4ml/kg/day orally for 4 weeks) + CPFX (80mg/kg/day orally for 2 weeks), starting on the first day of the third week. Finally, Serum and tissue specimens are collected at the conclusion of the experiment for biochemical and histopathological examination. Results: It ended up being found in the CPFX-treated group. ALT [iii], AST [iv], and TNFÎ±[v] levels were all significantly elevated in the serum. While this medication reduced the hepatocellular content of GSH [vi], it increased the tissue content of MDA [vii], which clearly shows oxidative stress Reduced BCL2[viii] levels also indicate the presence of apoptosis. CPFX causes an increase in kidney-specific markers such as creatinine and urea, indicating kidney disease. When PSO was combined with CPFX BAX [ix], MDA, AST, ALT, and TNFÎ± levels were considerably reduced, while GSH and BCL2 levels increased, indicating that PSO has antioxidant action and reduces apoptosis. Additionally, the renal function parameters improved, as seen by lower serum creatinine and urea levels. Conclusion: In rats, employing PSO as a concurrent prophylactic therapy while administering CPFX effectively reduced CPFX-induced oxidative stress and apoptotic damage. PSO could be used as a preventive medication to prevent CPFX-induced cellular damage to the kidneys and liver. Â Â Â